Implementasi UU Nomor 1 Tahun 1974 dan Kompilasi Hukum Islam dalam Pemenuhan Hak-Hak Anak Pasca Perceraian di Ponorogo - Hafit Ibnu Malik; Agus Purnomo (Journal of Economics, Law, and Humanities, 2022)
Children are the most sacrificed figures in divorce, whether they lack love or material fulfilment. This qualitative research with descriptive-analytical research type with the theory of legal effectiveness aims to analyze the implementation and implications of Article 41 of Law No. 1 of 1974 Article 156 of the Compilation of Islamic Law (KHI) on the fulfilment of children's rights after divorce in Ponorogo. The results of this study indicate that the judge who decided on case number 1657/Pdt.G/2019/PA.PO and case number 1371/Pdt.G/2019/PA.PO was appropriate and in line with its implementation and its impact on a father to remain fulfilled or provide a living or the rights of their children according to their abilities. This means that the decision is carried out in accordance with what is in the law and is carried out entirely by the litigants so that the decision is effective in its implementation.